Electrospun pva-graphene oxide-pedot: PSS nanofibers for wound healing - Barthasarathy, Piravin Raj; Ahmad Shahizam, Zayd; Wan Salim, Wan Wardatul Amani (2019)
Electrical fiber spinning, or electrospinning is a common technique adopted to produce nanofibers (diameter ˂ 500 nm) [1]. Nanofibers-based scaffolds are highly valued for their mechanical and biological properties [1]. Nanofibers composed of different nanofillers posed enormous challenges in emulating the architecture of the extracellular matrix [1]. We have capitalized on the unique property of graphene oxide (GO) and poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS) as nanofillers. GO has been used as a carrier for drug [2] & gene delivery [3] and wound healing applications [4]. SH-SY5Y neuroblastoma-derived cells and primary mouse embryonic neural cells were able to survive upon attachment to PEDOT:PSS [5]. PEDOT:PSS polymers can also act as a drug delivery platform [6].